Calmodulin-induced Conformational Control and Allostery Underlying Neuronal Nitric Oxide Synthase Activation. Issue 7 (30th March 2018) - Hanson, Quinlin M.; Carley, Jeffrey R.; Gilbreath, Tyler J.; Smith, Brian C.; Underbakke, Eric S.
Abstract: Nitric oxide synthase (NOS) is the primary generator of nitric oxide signals controlling diverse physiological processes such as neurotransmission and vasodilation. NOS activation is contingent on Ca 2 + /calmodulin binding at a linker between its oxygenase and reductase domains to induce large conformational changes that orchestrate inter-domain electron transfer. However, the structural dynamics underlying activation of full-length NOS remain ambiguous. Employing hydrogen–deuterium exchange mass spectrometry, we reveal mechanisms underlying neuronal NOS activation by calmodulin and regulation by phosphorylation. We demonstrate that calmodulin binding orders the junction between reductase and oxygenase domains, exposes the FMN subdomain, and elicits a more dynamic oxygenase active site. Furthermore, we demonstrate that phosphorylation partially mimics calmodulin activation to modulate neuronal NOS activity via long-range allostery. Calmodulin binding and phosphorylation ultimately promote a more dynamic holoenzyme while coordinating inter-domain communication and electron transfer. Graphical abstract: Highlights: Mechanisms of nitric oxide synthase (NOS) activation and regulation are ambiguous. Ca 2 + /calmodulin (CaM) and phosphorylation regulate nNOS function. H/D exchange MS dissects structural mechanism of nNOS activation and regulation. CaM induces FMN subdomain conformational changes via linker ordering. CaM allows allosteric communication between reductase and oxygenase domains. Phosphomimetics prime nNOS for activity independent of CaM.